2021
DOI: 10.1186/s12909-021-02772-y
|View full text |Cite
|
Sign up to set email alerts
|

Research activities and critical appraisal skills among Saudi orthopedic residents

Abstract: Background Medical research is a central part of any residency training. In view of the new Saudi orthopedic committee promotion regulation that mandates each resident to participate in a research project, the challenges that stand in the way of completion of substantial research within surgical residency must be investigated. The aim of this study was to assess the practice, attitudes, perception, and limitations associated with research among residents in the Saudi orthopedic program in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…In another Saudi investigation, Al-Mohrej et al . [ 16 ] reported that 95% of their orthopedic residents participated in research activities during their residency program. These differences may be attributable to the nature of the work and the availability of proper supervision and cooperation in these departments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another Saudi investigation, Al-Mohrej et al . [ 16 ] reported that 95% of their orthopedic residents participated in research activities during their residency program. These differences may be attributable to the nature of the work and the availability of proper supervision and cooperation in these departments.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the literature regarding the significance of the participants’ demographics is conflicting among studies in different global settings. [ 16 18 ] This may be attributable to the differences in the baseline characteristics and conditions that some residents can be subjected to over others, including previous exposure to education campaigns and the presence of cooperative supervisions for the corresponding residents. Therefore, further larger investigations are needed for increased understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a number of studies highlighted the research experience in residency training. [10,15] A multicenter study in Saudi Arabia shows that although residents have a positive attitude toward research, a large majority of residents are facing obstacles in conducting research. This study explains that residents' insu cient research skills is a major obstacle to pursue research.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17,19] The current de ciency to theorize learning of residents undermines the transformative dynamics of learning and its multilayered mechanisms. In addition, the existing body of research overlooks the complexity of learning, focusing on limited aspects of residents' experiences, such as their learning preferences [16] , perception of research experiences [10,15] , and burnout. [9,10] None of these studies have utilized qualitive methods to collect data, and thus, not capturing the complexity of learning in residency education.…”
Section: Introductionmentioning
confidence: 99%